Age is a critical determinant in recovery from multiple sclerosis relapses - Conway, Brittani L; Zeydan, Burcu; Uygunoğlu, Uğur; Novotna, Martina; Siva, Aksel; Pittock, Sean J; Atkinson, Elizabeth J; Rodriguez, Moses; Kantarci, Orhun H (Multiple sclerosis, 2019)
OBJECTIVE: To evaluate the impact of age on recovery from multiple sclerosis relapses. BACKGROUND: Increasing disability in multiple sclerosis is a consequence of progressive disease and incomplete relapse recovery. METHODS: The first and last-ever relapse data (357 relapses in 193 patients) from the Olmsted County population-based multiple sclerosis cohort were systematically reviewed for age, fulminance, location (optic nerve, brainstem/cerebellar, spinal cord), peak deficit, and maximum recovery. Three different relapse-outcome measures were studied both as paired analyses and as an overall group effect: change from peak deficit to maximum recovery in raw functional system score related to the relapse (ΔFSS), a previously published FSS-based relapse-impact model, and change from peak deficit to maximum recovery in Extended Disability Status Scale (ΔEDSS) score. RESULTS: Older age was linearly associated with worse recovery in the ΔFSS outcome (p = 0.002), ΔEDSS outcome (p < 0.001), and the FSS-based relapse-impact model (p < 0.001). A multivariate analysis of ΔFSS outcome linked poor recovery to older age (p = 0.015), relapse location (transverse myelitis or brainstem/cerebellar syndrome; p < 0.001), and relapse fulminance (p = 0.004). CONCLUSION: Multiple sclerosis-relapse recovery declines in a linear fashion with increased age, which should be considered when making treatment decisions.
Keywords: recidiva; Humans; lidé středního věku; Disease Progression; Female; dospělí; věkové faktory; lidé; obnova funkce; Adult; Multiple Sclerosis, Relapsing-Remitting; ženské pohlaví; relabující-remitující roztroušená skleróza; Male; Middle Aged; Recovery of Function; Recurrence; progrese nemoci; Age Factors; mužské pohlaví